Microstructure influenced variation in the local surface electrical heterogeneity in thickening Al-doped ZnO films: Evidence using both scanning tunnelling spectroscope and conductive atomic force microscope. (1st March 2018) - Patel, Tvarit A.; Singh, Chetan C.; Panda, Emila
Abstract: In this study, variation in the local surface electrical heterogeneity within and also for a thickening Al-doped ZnO film is studied using both the Conductive atomic force microscope/Spectroscope (C-AFM/C-AFS) and Scanning Tunnelling Microscope/Spectroscope (STM/STS) techniques. To this end, these films were deposited by varying the deposition time from 15 to 120 min by RF magnetron sputtering. The local surface electrical heterogeneity was found to be strongly dependent on the overall microstructure of the film grown at a particular deposition time. X-ray Photoelectron Spectroscope (XPS) and Transmission Electron Microscope-Energy Dispersive Spectroscope (TEM-EDS) were used to discern the distribution of the chemical constituents over these film surfaces. This study correlates the presence of a large amount of chemisorbed oxygen and/or segregated Alx Oy at the grain boundaries associated with relatively non-uniform and/or rough films to the overall lower surface current values. Subsequently, a uniformly thick AZO film with a homogenous microstructure grown at an optimum deposition time is found to have the least amount of chemisorbed oxygen along with an effective distribution of Al doping on the film surface, leading to an increase in the overall surface current. This higher surface current is then found to increase the surface electrical heterogeneity of the film due to increased difference between a defect and defect-free region, contrary for a non-uniform and/or rough film.